A Census of Atmospheric Variability From Seconds to Decades. Issue 21 (15th November 2017) - Williams, Paul D.; Alexander, M. Joan; Barnes, Elizabeth A.; Butler, Amy H.; Davies, Huw C.; Garfinkel, Chaim I.; Kushnir, Yochanan; Lane, Todd P.; Lundquist, Julie K.; Martius, Olivia; Maue, Ryan N.; Peltier, W. Richard; et al.
Abstract: This paper synthesizes and summarizes atmospheric variability on time scales from seconds to decades through a phenomenological census. We focus mainly on unforced variability in the troposphere, stratosphere, and mesosphere. In addition to atmosphere‐only modes, our scope also includes coupled modes, in which the atmosphere interacts with the other components of the Earth system, such as the ocean, hydrosphere, and cryosphere. The topics covered include turbulence on time scales of seconds and minutes, gravity waves on time scales of hours, weather systems on time scales of days, atmospheric blocking on time scales of weeks, the Madden–Julian Oscillation on time scales of months, the Quasi‐Biennial Oscillation and El Niño–Southern Oscillation on time scales of years, and the North Atlantic, Arctic, Antarctic, Pacific Decadal, and Atlantic Multidecadal Oscillations on time scales of decades. The paper serves as an introduction to a special collection of Geophysical Research Letters on atmospheric variability. We hope that both this paper and the collection will serve as a useful resource for the atmospheric science community and will act as inspiration for setting future research directions. Key Points: The state of the atmosphere is observed to vary naturally on all time scales from seconds to decades and longer This paper synthesizes and summarizes that variability through a phenomenological census The paper provides an authoritative, concise, and accessible point of reference for the most important modes of atmospheric variability